Towards a More Employment-Intensive and Pro-Poor Economic Growth in Bolivia - Luis Carlos Jemio; Maria del Carmen Choque (Institute for Advanced Development Studies (INESAD), 2006)
The reform program and growth pattern exhibited by the Bolivian economy in the last decade did not favour employment creation and consequently not an effective reduction of poverty. During the last decade, those sectors where the bulk of employment is concentrated, presented the lowest growth rates of GDP, labour productivity and real incomes. The present paper analyzes in detail the two sectors where the bulk of employment and poverty is concentrated (agriculture and the urban informal sector) in order to determine the critical constraints to improvements in productivity, employment generation, and reductions in poverty.
Keywords: J24; O54; o17; 330; Employment; Poverty; Growth; Bolivia